2010
DOI: 10.1155/2011/803015
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by the Traditional Chinese Medicine, Tao‐Hong‐Si‐Wu‐Tang, against Middle Cerebral Artery Occlusion‐Induced Cerebral Ischemia in Rats

Abstract: Tao-Hong-Si-Wu-Tang (THSWT) is a famous traditional Chinese medicine (TMC). In the present study, oral administration of THSWT (0.7 and 1.4 g kg−1day−1) for 14 days before MCAO dose-dependently attenuated focal cerebral ischemia in rats. MCAO-induced focal cerebral ischemia was associated with increases in hypoxia-inducible factor (HIF)-1α, inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF)-α, and active caspase-3 expressions in ischemic regions. These expressions were obviously inhibited by 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…Our previous study showed that THSWD could regulate the angiogenesis of chick chorioallantoic membrane, indicating the potential application for the recovery after cerebral ischemia [7]. Another previous study has verified that THSWD exhibited neuroprotective activity against cerebral ischemia-reperfusion-induced injury [8]. The present study also confirmed this by discovering THSWD mediated protection against OGD-Rep induced injury in PC12 cells.…”
Section: Discussionsupporting
confidence: 82%
“…Our previous study showed that THSWD could regulate the angiogenesis of chick chorioallantoic membrane, indicating the potential application for the recovery after cerebral ischemia [7]. Another previous study has verified that THSWD exhibited neuroprotective activity against cerebral ischemia-reperfusion-induced injury [8]. The present study also confirmed this by discovering THSWD mediated protection against OGD-Rep induced injury in PC12 cells.…”
Section: Discussionsupporting
confidence: 82%
“…THSWD has been used to treat rabbits in a model of SANFH, resulting in reduced blood viscosity, increased regeneration of local microvessels, improved local blood supply, and facilitation of the recovery of the necrotic femoral head (21,22). THSWD appears to be closely associated with regulation of HIF-1α, and HIF-1α is reported to prevent the occurrence of SANFH (1,23). However, few systematic studies have consolidated the aforementioned findings, and whether THSWD affects SANFH via the HIF-1α signaling pathway is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…Although tissue-type plasminogen activator (t-PA) has been approved by FDA to treat stroke patients, this therapeutic strategy is confronted with ill side effects and is limited to patients within 3 hours of a stroke. Traditional Chinese herbal medicines have been used in ancient medicine systems as treatments for various ailments associated with stroke and have exhibited their special neuroprotective benefits on cerebral ischemia for centuries (Chen, 2012;Jaffer et al, 2011;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%